Evaluation of the clinical efficacy of muscle regions of meridians needling method for refractory facial paralysis based on infrared thermal imaging technology - Mao, Ting-li; Wang, Zhu-xing; Tian, Feng-wei; Zhou, Xi (Journal of acupuncture and tuina science, 2021)
Objective To explore the clinical efficacy of muscle regions of meridians needling method for refractory facial paralysis affecting different locations. Methods A total of 110 participants were randomized into an observation group and a control group, with 55 cases in each group. The observation group was treated with muscle regions of meridians needling method, and the control group was treated with conventional facial three-line needling method. The clinical efficacy was evaluated four weeks after the treatment. And the infrared imaging spectra of the two groups were examined. Results The total effective rate of the observation group was higher than that of the control group ( P <0.05), and its curative effect for refractory facial paralysis located above the geniculate ganglion was better than that of the control group ( P <0.05). The color scale distribution of different disease locations in the two groups varied significantly ( P <0.05), the higher the disease location, the higher the occurrence rate of cool zone and low temperature zone. After treatment, the reductions of the facial and periotic temperature difference between the healthy side and the affected side in the observation group were statistically different from those in the control group ( P <0.05). Conclusion Muscle regions of meridians needling method has a better effect than facial three-line needling method for refractory facial paralysis. It can promote the microcirculation of the affected side of the face, improve the blood and oxygen supply to local tissues, and thus promote the repair of the peripheral facial nerve.